2010
DOI: 10.1097/rlu.0b013e3181d6677c
|View full text |Cite
|
Sign up to set email alerts
|

Ga-68 DOTATOC PET, Endoscopic Ultrasonography, and Multidetector CT in the Diagnosis of Duodenopancreatic Neuroendocrine Tumors

Abstract: EUS, Ga-68 DOTATOC PET, and MDCT seem to have comparable accuracy in diagnosis of duodenopancreatic NET and their combination may allow an optimal preoperative diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
48
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 24 publications
0
48
1
Order By: Relevance
“…However, because of the better sensitivity, spatial resolution, and inherently quantitative nature of PET, somatostatin receptor imaging (SRI) with PET is increasingly used. Most common is the use of the 68 Ga-labeled somatostatin analogs, for example, 68 Ga-DOTATATE (6)(7)(8)(9), 68 Ga-DOTATOC (10)(11)(12), and 68 Ga-DOTANOC (13). However, the high positron energy of 68 Ga limits spatial resolution and the short half-life of 68 min may be challenging logistically, because production has to be aligned with patients and to be repeated several times a day.…”
mentioning
confidence: 99%
“…However, because of the better sensitivity, spatial resolution, and inherently quantitative nature of PET, somatostatin receptor imaging (SRI) with PET is increasingly used. Most common is the use of the 68 Ga-labeled somatostatin analogs, for example, 68 Ga-DOTATATE (6)(7)(8)(9), 68 Ga-DOTATOC (10)(11)(12), and 68 Ga-DOTANOC (13). However, the high positron energy of 68 Ga limits spatial resolution and the short half-life of 68 min may be challenging logistically, because production has to be aligned with patients and to be repeated several times a day.…”
mentioning
confidence: 99%
“…The superiority of 68 Ga-labeled somatostatin analogs in terms of specificity, sensitivity, staging accuracy, detection rate, quantification, and acquisition time over 18 F-FDG (5), 18 F-3,4-dihydroxyphenylalanine (6), 123 Imetaiodobenzylguanidine (7,8), 111 In-DTPA-pentetreotide (9), 18 F-NaF, and 99m Tc-dicarboxypropanediphosphonate (10) has been demonstrated. The high impact of 68 Ga PET/CT on patient management can be illustrated by the fact that the course of treatments was changed or adjusted in 50%-60% of cases on the basis of 68 Ga PET/CT results (11)(12)(13)(14)(15). Thorough analysis of the publications on 16 clinical studies involving 567 patients with suspected thoracic or gastroenteropancreatic NETs suggested PET/CT with 68 Galabeled somatostatin analogs as an independent first-line diagnostic imaging method for this category of patients (16).…”
mentioning
confidence: 99%
“…Ninety (62%) pNENs detected by conventional imaging were missed by Ga-68-DOTATOC-PET/CT. However, Ga-68-DOTATOC-PET/CT detected more liver and lymph node metastases in patients with known metastatic disease, which was already reported for sporadic metastatic pNENs (Versari et al 2010). Based on the available data, somatostatin PET/CT imaging cannot be recommended for routine screening of MEN1 patients, but it probably provides important additional information in patients with suspected or known metastatic disease.…”
Section: :10mentioning
confidence: 86%